2020
DOI: 10.5530/pj.2020.12.201
|View full text |Cite
|
Sign up to set email alerts
|

Garlic and its Active Compounds: A Novel Strategy to Fight Diseases Through Modulating Biological Activities

Faris Alrumaihi

Abstract: Throughout history, many plants and their products have been widely used as medicines for the prevention and treatment of different diseases in many cultures. Garlic (Allium sativum), is commonly used as a spice and traditionally used for its medicinal value since ancient times. Recent studies support the effects of garlic and its extracts in a wide range of applications. Due to the presence of sulfur containing compounds, high trace mineral content and enzymes, garlic has been reported to have implications in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…Allicin is one of the main active constituents in garlic [ 36 , 37 ], but it is highly unstable and is quickly decomposed in other stable organosulfur constituents, such as diallyl disulfide [ 33 ]. Alrumaihi [ 38 ] highlighted that allicin and diallyl disulfide are important active compounds that modulate several biological activities and help prevent pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Allicin is one of the main active constituents in garlic [ 36 , 37 ], but it is highly unstable and is quickly decomposed in other stable organosulfur constituents, such as diallyl disulfide [ 33 ]. Alrumaihi [ 38 ] highlighted that allicin and diallyl disulfide are important active compounds that modulate several biological activities and help prevent pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, ethanolic and aqueous extracts of A. sativum exhibited significant fibrinolytic activity [37]. A study [38] revealed that A. sativum triggers the fibrinolytic activity by enhancing the activation of t-PA (tissue-type plasminogen activation) mediated plasminogen and also, reduces the thrombin formation by suppressing coagulation system. Diallyl trisulphide and diallyl disulphide exhibit less platelet thromboxane formation and antiplatelet activity than the placebo.…”
Section: Blood Protection Activitymentioning
confidence: 99%
“…Comparatively, multiple studies have proven that antiinflammatory agents can decrease the levels of inflammatory cytokines. 41,42 Therefore, treatment with garlic is expected to reduce the exacerbations of hepatitis and improve the quality of patient's life in numerous inflammatory diseases. 43 Garlic is a natural product with antioxidant, anti-inflammatory, anti-apoptotic, and antimicrobial properties.…”
mentioning
confidence: 99%